Detection of Viral-like Particles by Electron Microscopy of Negatively Stained Extracts from Grapevines - Corbetta, M. K.; Kasdorf, G. G. F.; Engelbrecht, D. J.; Wiid, J. (South African Journal of Enology and Viticulture, 2017)
Viral-like particles were detected by electron microscopy of negatively stained extracts from young leaves and roots of grapevines infected with fanleaf virus and purported to be infected with the graft-transmissible agents of Ieafroll, corky bark, fleck, and stem grooving. Preparations were extracted in 0.01 M phosphate buffer (pH 7.0) containing 2.5% nicotine and negatively stained with 2% ammonium molydate. Membrane associated spherical particles were detected in extracts from grapevines that tested positive for fanleaf virus by ELISA and bioassay. Similar membrane associated particles were detected in herbaceous plants inoculated with grapevine extracts. Rigid rod tobacco mosaic virus-like particles were detected in extracts from some grapevines but they were not disease associated. Flexuous rod viral-like particles about 11x800 nm with cross-banding helical substructure similar to closteroviruses were detected in extracts from leafroll infected grapevines.